Asymmetric price transmission in the Chinese pork and pig market. Issue 1 (2nd January 2018) - Dong, Xiaoxia; Brown, Colin; Waldron, Scott; Zhang, Jing
Abstract : Purpose: The purpose of this paper is to analyze price transmission in the Chinese pork market between 1994 and 2016 and examine any incidence and causes of asymmetric price transmission. Design/methodology/approach: The approach uses threshold autoregressive models, asymmetric error correction models and autoregressive moving average models to examine the price transmission using monthly pig and pork prices from 1994 to 2016. Findings: While a symmetric price transmission between pork and pig prices was identified for the period between June 1994 and June 2007, an asymmetric price transmission response between pork and pig prices was found for the period July 2007 to June 2016. Key factors behind the asymmetric price transmission include the chicken price and China's provisional purchasing and stockpiling policy which is having a counter-productive impact on prices. Originality/value: The paper contributes to the literature by examining price transmission in two different periods: 1994 to 2007 where prices are lower and more stable; and 2007 to 2016 where prices are higher and volatile. The paper examines the impact of production and market policies on price transmission in the Chinese pork and pig market, with several policy implications.